Low‐Cost and Highly Efficient Carbon‐Based Perovskite Solar Cells Exhibiting Excellent Long‐Term Operational and UV Stability. Issue 49 (31st October 2019) - Arora, Neha; Dar, M. Ibrahim; Akin, Seckin; Uchida, Ryusuke; Baumeler, Thomas; Liu, Yuhang; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract: Today's perovskite solar cells (PSCs) mostly use components, such as organic hole conductors or noble metal back contacts, that are very expensive or cause degradation of their photovoltaic performance. For future large‐scale deployment of PSCs, these components need to be replaced with cost‐effective and robust ones that maintain high efficiency while ascertaining long‐term operational stability. Here, a simple and low‐cost PSC architecture employing dopant‐free TiO2 and CuSCN as the electron and hole conductor, respectively, is introduced while a graphitic carbon layer deposited at room temperature serves as the back electrical contact. The resulting PSCs show efficiencies exceeding 18% under standard AM 1.5 solar illumination and retain ≈95% of their initial efficiencies for >2000 h at the maximum power point under full‐sun illumination at 60 °C. In addition, the CuSCN/carbon‐based PSCs exhibit remarkable stability under ultraviolet irradiance for >1000 h while under similar conditions, the standard spiro‐MeOTAD/Au based devices degrade severely. Abstract : A simple perovskite solar cell architecture, which is based on dopant‐free electron and hole conductors and carbon back contact deposited at room temperature, is demonstrated. The resulting architecture leads to the fabrication of cheap and highly efficient perovskite solar cells exhibiting unprecedented long‐term operational and UV stability thus hold immense potential for large‐scale deployment.